Placental magnetic resonance imaging: normal appearance, anatomical variations, and pathological findings - Novis, Maria Inês (Radiol Bras, 2021)
Placental magnetic resonance imaging (MRI) has been increasingly requested, especially for the evaluation of suspected cases of placental adhesive disorders, generally known as placenta accreta. Abdominal radiologists need to become familiar with normal placental anatomy, anatomical variations, the current terminology, and major placental diseases that, although rare, are important causes of maternal and fetal morbidity and mortality. The aim of this didactic pictorial essay is to illustrate various findings on placental MRI, as well as to emphasize the importance of communication between radiologists and obstetricians in the search for best practices in the management of the affected patients.